FlyHealth: Aviation Medical Management and Services - Rajendran, Vimalan; MOHD YASIN, SUHAILA (Applied Information Technology And Computer Science, 2024)
Aviation medicine's critical role in ensuring aviation professionals' safety is marred by challenges at Poliklinik Primecare. Fragmented patient data, complex financial reports, and inefficient appointment reminders hinder patient care, operational efficiency, and financial transparency. Addressing these issues, "FLYHEALTH: Aviation Medical Management and Services" introduces a web-based system with three objectives: design, development, and testing. The innovative system centralizes patient data, streamlines financial reporting, and enhances appointment reminders. By prioritizing user experience, FLYHEALTH aims to transform aviation medical management, ensuring accuracy, timeliness, and seamless coordination for heightened safety and efficiency. The FlyHealth project is adopting the Agile methodology in aviation medical care management. FlyHealth's transformative impact extends to optimizing pharmaceutical inventory management, unifying patient records, streamlining financial reporting, and implementing an automated appointment reminder system. This comprehensive approach underscores its commitment to enhancing the effectiveness and safety of aeromedical procedures, setting new standards for excellence in aviation medicine.